Hypoxia-Ischemia and Hypothermia Independently and Interactively Affect Neuronal Pathology in Neonatal Piglets with Short-Term Recovery - O'Brien, Caitlin E; Santos, Polan T; Kulikowicz, Ewa; Reyes, Michael; Koehler, Raymond C; Martin, Lee J; Lee, Jennifer K (Developmental neuroscience, 2019)
Therapeutic hypothermia is the standard of clinical care for moderate neonatal hypoxic-ischemic encephalopathy. We investigated the independent and interactive effects of hypoxia-ischemia (HI) and temperature on neuronal survival and injury in basal ganglia and cerebral cortex in neonatal piglets. Male piglets were randomized to receive HI injury or sham procedure followed by 29 h of normothermia, sustained hypothermia induced at 2 h, or hypothermia with rewarming during fentanyl-nitrous oxide anesthesia. Viable and injured neurons and apoptotic profiles were counted in the anterior putamen, posterior putamen, and motor cortex at 29 h after HI injury or sham procedure. Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) identified genomic DNA fragmentation to confirm cell death. Though hypothermia after HI preserved viable neurons in the anterior and posterior putamen, hypothermia prevented neuronal injury in only the anterior putamen. Hypothermia initiated 2 h after injury did not protect against apoptotic cell death in either the putamen or motor cortex, and rewarming from hypothermia was associated with increased apoptosis in the motor cortex. In non-HI shams, sustained hypothermia during anesthesia was associated with neuronal injury and corresponding viable neuron loss in the anterior putamen and motor cortex. TUNEL confirmed increased neurodegeneration in the putamen of hypothermic shams. Anesthetized, normothermic shams did not show abnormal neuronal cytopathology in the putamen or motor cortex, thereby demonstrating minimal contribution of the anesthetic regimen to neuronal injury during normothermia. We conclude that the efficacy of hypothermic protection after HI is region specific and that hypothermia during anesthesia in the absence of HI may be associated with neuronal injury in the developing brain. Studies examining the potential interactions between hypothermia and anesthesia, as well as with longer durations of hypothermia, are needed.